(untitled) (Modern American Journal of Biological and Environmental Sciences, 2025)
Pre-harvest fruit bagging is a horticultural practice used to improve the external quality of apples, but its effects on the internal attributes essential for juice production are complex. This study was conducted to evaluate the influence of different colored paper bags on the quantitative and organoleptic parameters of juice from ‘Starcrimson’ and ‘Mutsu’ apple cultivars.